PEDOT–CNT Composite Microelectrodes for Recording and Electrostimulation Applications: Fabrication, Morphology, and Electrical Properties - Gerwig, Ramona; Fuchsberger, Kai; Schroeppel, Birgit; Link, Gorden S.; Heusel, Gerhard; Kraushaar, Udo; Schuhmann, Wolfgang; Stett, Alfred; Stelzle, Martin (Frontiers in Neuroengineering, 2012)
Composites of carbon nanotubes and poly(3,4-ethylenedioxythiophene) (PEDOT) and layers of PEDOT are deposited onto microelectrodes by electropolymerization of ethylenedioxythiophene in the presence of a suspension of carbon nanotubes and polystyrenesulfonate. Analysis by FIB and SEM demonstrate that CNT-PEDOT composites exhibit a porous morphology whereas PEDOT layers are more compact. Accordingly, capacitance and charge injection capacity of the composite material exceed those of pure PEDOT layers. In vitro cell culture experiments reveal excellent biocompatibility and mechanical stability of both PEDOT and PEDOT-CNT electrodes. Signals recorded from heart muscle cells demonstrate the high S/N ratio achievable with these electrodes. Long-term pulsing experiments confirm stability of charge injection capacity. In conclusion, a robust fabrication procedure for composite PEDOT-CNT electrodes is demonstrated and results show that these electrodes are well suited for stimulation and recording in cardiac and neurophysiological research.